Klatskin tumor (hilar cholangiocarcinoma) - Reddy Ravikanth; Denver Steven Pinto (Apollo Medicine, 2018)
Klatskin tumor is a term that was given to a hilar cholangiocarcinoma, occurring at the bifurcation of the common hepatic duct. Typically, these tumors are small, poorly differentiated, exhibit aggressive biologic behavior, and tend to obstruct the intrahepatic bile ducts. Here, we present the multidetector computed tomography findings in a case of hilar cholangiocarcinoma.